An inside job: how endosomal Na+/H+ exchangers link to autism and neurological disease - Kondapalli, Kalyan C.; Prasad, Hari; Rao, Rajini (Frontiers in Cellular Neuroscience, 2014)
Autism imposes a major impediment to childhood development and a huge emotional and financial burden on society. In recent years, there has been rapidly accumulating genetic evidence that links the eNHE, a subset of Na+/H+ exchangers that localize to intracellular vesicles, to a variety of neurological conditions including autism, attention deficit hyperactivity disorder, intellectual disability and epilepsy. By providing a leak pathway for protons pumped by the V-ATPase, eNHE determine luminal pH and regulate cation (Na+, K+) content in early and recycling endosomal compartments. Loss-of-function mutations in eNHE cause hyperacidification of endosomal lumen, as a result of imbalance in pump and leak pathways. Two isoforms, NHE6 and NHE9 are highly expressed in brain, including hippocampus and cortex. Here, we summarize evidence for the importance of luminal cation content and pH on processing, delivery and fate of cargo and on the surface expression and function of membrane receptors and neurotransmitter transporters, drawing upon insights from model organisms and mammalian cells. These studies lead to cellular models of eNHE activity in pre- and post-synaptic neurons and astrocytes, where they could impact synapse development and plasticity. The study of eNHE has provided new insight on the mechanism of autism and other debilitating neurological disorders and opened up new possibilities for therapeutic intervention.